VPN Solution for Zoomfinance.com : Toward Cost Saving and Security Exercise - Sia, Sie Tung (2003)
Many companies and organizations nowadays uses Virtual Private Network (VPN) as a solution, which enable them to save cost and create more secure environment. The VPN market has changed significantly in the past ten years as the Internet has grown and more companies have come to rely on it for communications. This report will look at VPN as a means of user to access private network resources securely over the Internet. Then I will look on the part of technologies for VPNs used today on the Internet including tunneling, authentication, access control and data security. Beside, this report will also including VPN architectures, and topologies. For integrated VPN security I will describe and setting up firewall, encrypted data tunnel and also Intrusion Detection System (IDS). Lastly, testing tools and result will be administered on the new configuration.